2000
DOI: 10.1210/endo.141.11.7753
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Calcimimetic Compound and Naturally Activating Mutations on the Human Ca2+Receptor and on Ca2+Receptor/Metabotropic Glutamate Chimeric Receptors

Abstract: Naturally occurring mutations identified in subjects with autosomal dominant hypocalcemia (ADH) and the calcimimetic compound, R-568, have both been reported to increase Ca2+ sensitivity of the Ca2+ receptor (CaR). To gain insight into their mechanism of action, we studied interactions between four different ADH mutations located in the amino-terminal extracellular domain (ECD) and R-568. We found that R-568 increased the sensitivity of three of the ADH mutant receptors, but the Leu125Pro mutant appeared to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(19 citation statements)
references
References 23 publications
1
17
0
1
Order By: Relevance
“…In parathyroid tissue, they decrease the threshold for CaSR activation by extracellular calcium ions and diminish PTH secretion directly without aggravating disturbances in mineral metabolism that have been associated with adverse clinical outcomes [52]. The calcimimetic agent, NPS-568, has been shown to act specifically on the calcium receptor's 7 transmembrane domain [53].…”
Section: Therapeutic Consequencesmentioning
confidence: 99%
“…In parathyroid tissue, they decrease the threshold for CaSR activation by extracellular calcium ions and diminish PTH secretion directly without aggravating disturbances in mineral metabolism that have been associated with adverse clinical outcomes [52]. The calcimimetic agent, NPS-568, has been shown to act specifically on the calcium receptor's 7 transmembrane domain [53].…”
Section: Therapeutic Consequencesmentioning
confidence: 99%
“…The hCaR belongs to the structurally unique family 3 characterized by very large amino-terminal extracellular domains (ECDs) that includes metabotropic glutamate receptors (mGluR1-8), putative pheromone receptors of the vomeronasal organ, sweet taste receptors 1-3, and ␥-aminobutyric acid B receptors. Studies of chimeric receptors containing hCaR ECD and mGluR1 7TM domains have confirmed that hCaR ECD confers responsiveness to [Ca 2ϩ ] o on the chimeric receptors (5,6). This defines a ligand-binding role similar to that defined for the ECD structures of mGluR1 and other family 3 receptors (7).…”
mentioning
confidence: 76%
“…An hCaR mutant 7TM construct lacking the ECD (T903-Rhoc) responds to [Ca 2ϩ ] o and other di-and poly-cations (5, 6, 9). Furthermore, (R)-N-(3-methoxy-␣-phenylethyl)-3-(2Ј-chlorophenyl)-1-propylamine hydrochloride (NPS-R568), an allosteric calcimimetic compound, synergistically enhances these cationic responses (5,6,9).An acidic residue (Glu837) located in extracellular loop (EL) 3 of the 7TM has been reported to interact with NPS-R568 but might not be involved in Ca 2ϩ binding (10). We had previously hypothesized that a cluster of acidic residues in…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely, however, that l-amino acids and phenylalkylamines interact with different portions of the CaSR. Whereas l-amino acids interact with specific loci in the extracellular domain as mentioned previously, calcimimetic agents bind most likely to the membrane-spanning portion of the receptor (39).…”
Section: Structural and Functional Components Of The Casr And The Regmentioning
confidence: 88%